Population-level impact and herd effects following the introduction of human papillomavirus vaccination programmes: updated systematic review and meta-analysis. Issue 10197 (10th August 2019) - Drolet, Mélanie; Bénard, Élodie; Pérez, Norma; Brisson, Marc; ,
Summary: Background: More than 10 years have elapsed since human papillomavirus (HPV) vaccination was implemented. We did a systematic review and meta-analysis of the population-level impact of vaccinating girls and women against human papillomavirus on HPV infections, anogenital wart diagnoses, and cervical intraepithelial neoplasia grade 2+ (CIN2+) to summarise the most recent evidence about the effectiveness of HPV vaccines in real-world settings and to quantify the impact of multiple age-cohort vaccination. Methods: In this updated systematic review and meta-analysis, we used the same search strategy as in our previous paper. We searched MEDLINE and Embase for studies published between Feb 1, 2014, and Oct 11, 2018. Studies were eligible if they compared the frequency (prevalence or incidence) of at least one HPV-related endpoint (genital HPV infections, anogenital wart diagnoses, or histologically confirmed CIN2+) between pre-vaccination and post-vaccination periods among the general population and if they used the same population sources and recruitment methods before and after vaccination. Our primary assessment was the relative risk (RR) comparing the frequency (prevalence or incidence) of HPV-related endpoints between the pre-vaccination and post-vaccination periods. We stratified all analyses by sex, age, and years since introduction of HPV vaccination. We used random-effects models to estimate pooled relative risks. Findings: We identified 1702 potentially eligible articles for this systematic review and meta-analysis, and included 65 articles in 14 high-income countries: 23 for HPV infection, 29 for anogenital warts, and 13 for CIN2+. After 5–8 years of vaccination, the prevalence of HPV 16 and 18 decreased significantly by 83% (RR 0·17, 95% CI 0·11–0·25) among girls aged 13–19 years, and decreased significantly by 66% (RR 0·34, 95% CI 0·23–0·49) among women aged 20–24 years. The prevalence of HPV 31, 33, and 45 decreased significantly by 54% (RR 0·46, 95% CI 0·33–0·66) among girls aged 13–19 years. Anogenital wart diagnoses decreased significantly by 67% (RR 0·33, 95% CI 0·24–0·46) among girls aged 15–19 years, decreased significantly by 54% (RR 0·46, 95% CI 0.36–0.60) among women aged 20–24 years, and decreased significantly by 31% (RR 0·69, 95% CI 0·53–0·89) among women aged 25–29 years. Among boys aged 15–19 years anogenital wart diagnoses decreased significantly by 48% (RR 0·52, 95% CI 0·37–0·75) and among men aged 20–24 years they decreased significantly by 32% (RR 0·68, 95% CI 0·47–0·98). After 5–9 years of vaccination, CIN2+ decreased significantly by 51% (RR 0·49, 95% CI 0·42–0·58) among screened girls aged 15–19 years and decreased significantly by 31% (RR 0·69, 95% CI 0·57–0·84) among women aged 20–24 years. Interpretation: This updated systematic review and meta-analysis includes data from 60 million individuals and up to 8 years of post-vaccination follow-up. Our results show compelling evidence of the substantial impact of HPV vaccination programmes on HPV infections and CIN2+ among girls and women, and on anogenital warts diagnoses among girls, women, boys, and men. Additionally, programmes with multi-cohort vaccination and high vaccination coverage had a greater direct impact and herd effects. Funding: WHO, Canadian Institutes of Health Research, Fonds de recherche du Québec – Santé.